TINJAUAN YURIDIS TERHADAP PEMBAGIAN KEWENANGAN PRESIDEN DAN WAKIL PRESIDEN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Andry Hernandes; Mexsasai Indra; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
President is the executive in charge of government administration. In carryingout his duties the President is assisted by a Vice President. The position of thePresident and Vice President is in a balanced position because it is pronounced inone breath on the constitution which has prevailed in Indonesia. However, on theconstitution, the position of the Vice President as auxiliary to the President is notclearly regulated on his duties and authorities. The purpose of writing this thesis,namely: First, the division of the authority of the President and Vice President on theconstitutional system of the Republic of Indonesia, Second, the ideal arrangementrelated to the division of authority President and Vice President the Republic ofIndonesia in the future.This type of research can be classified in normative research that is researchthat discusses the principles of law, legal system, legal synchronization level, legalhistory and comparison of law.From the research results of the problem there are two main things can beconcluded. First, the President is accompanied by the Vice President in an equalposition in the constitutional structure of the Republic of Indonesia; Second, Incarrying out governmental duties in the executive field, the duties and authoritiesobtained by the President derive from the constitution, while the duties andauthorities of the Vice President are obtained from a joint agreement between thePresident and Vice President. Suggestion Writer, Firstly, Should be madeimprovements to the position of Vice President on the constitutional structure of theRepublic of Indonesia, with the aim to be more clearly related to the flow ofcoordination and communication, especially in the field of executive power. Second,the 1945 Constitution of the State of the Republic of Indonesia should be amended inrelation to the division of authority of the President and Vice President, affirming theposition of the Vice President in the constitutional structure of the Republic ofIndonesia, making the Law on the Presidential Institution as the exercise.Keywords: President - Vice President – Authority